Highly Reversible Lithiation of Additive Free T‐Nb2O5 for a Quarter of a Million Cycles - Wechsler, Sean Cade; Gregg, Alexander; Stefik, Morgan (Advanced functional materials, 2024)
Fast energy storage via intercalation requires quick ionic diffusion and often results in pseudocapacitive behavior. The cycling stability of such energy storage materials remains understudied despite the relevance to lifetime cost. Orthorhombic niobium oxide (T‐Nb2O5) is a rapid ion intercalation material with a theoretical capacity of 201.7 mAh g−1 (Li2Nb2O5) and good cycling stability due to the minimal unit cell strain during (de)intercalation. Prior reports of T‐Nb2O5 cycling between 1.3–3.1 V versus Li/Li+ noted a 50% loss in capacity after 10 000 cycles. Here, cyclic voltammetry is used to identify the role of the voltage window, state of charge, and potentiostatic holds on the cycling stability of mesoporous T‐Nb2O5 thin films. Films cycled between 1.2–3.0 V versus Li/Li+ without voltage holds (Li1.1Nb2O5) exhibited extreme cycling stability with 90.8% capacity retention after 0.25 million cycles without detectable morphological/crystallographic changes. In contrast, the inclusion of 60 s voltage holds (Li2.18Nb2O5) led to rapid capacity loss with 61.6% retention after 10 000 cycles with corresponding X‐ray diffraction evidence of amorphization. Cycling with other limited voltage windows identifies that most crystallographic degradation occurs at higher extents of lithiation. These results reveal remarkable stability over limited conditions and suggest that T‐Nb2O5 amorphization is associated with high extents of lithiation. Typical electrode materials can cycle for a few hundred to thousand cycles before an appreciable capacity loss occurs. Improving this cycling stability leads to proportionally reduced costs of energy storage. Using kinetically limited lithiation (see picture), T‐Nb2O5 thin films are cycled at high rates for 0.25 million cycles and retain an impressive 90.8% of the initial capacity. This improvement enabled a 25× increase in the number of report cycles as compared to similar electrodes.